Cyclin C-Cdk8 Kinase Phosphorylation of Rim15 Prevents the Aberrant Activation of Stress Response Genes - Willis, Stephen D.; Hanley, Sara E.; Doyle, Steven J.; Beluch, Katherine; Strich, Randy; Cooper, Katrina F. (Frontiers in Cell and Developmental Biology, 2022)
Cells facing adverse environmental cues respond by inducing signal transduction pathways resulting in transcriptional reprograming. In the budding yeast Saccharomyces cerevisiae, nutrient deprivation stimulates stress response genes (SRGs) transcription critical for entry into either quiescence or gametogenesis depending on the cell type. The induction of a subset of SRGs requires nuclear translocation of the conserved serine-threonine kinase Rim15. However, Rim15 is also present in unstressed nuclei suggesting that additional activities are required to constrain its activity in the absence of stress. Here we show that Rim15 is directly phosphorylated by cyclin C-Cdk8, the conserved kinase module of the Mediator complex. Several results indicate that Cdk8-dependent phosphorylation prevents Rim15 activation in unstressed cells. First, Cdk8 does not control Rim15 subcellular localization and rim15∆ is epistatic to cdk8∆ with respect to SRG transcription and the execution of starvation programs required for viability. Next, Cdk8 phosphorylates a residue in the conserved PAS domain in vitro. This modification appears important as introducing a phosphomimetic at Cdk8 target residues reduces Rim15 activity. Moreover, the Rim15 phosphomimetic only compromises cell viability in stresses that induce cyclin C destruction as well as entrance into meiosis. Taken together, these findings suggest a model in which Cdk8 phosphorylation contributes to Rim15 repression whilst it cycles through the nucleus. Cyclin C destruction in response to stress inactivates Cdk8 which in turn stimulates Rim15 to maximize SRG transcription and cell survival.